Numeracy in the making : twenty years of Australian adult numeracy - Johnston, Betty (Adult Literacy and Numeracy Australian Research Consortium., 2002)
What does the past tell us about adult literacy and numeracy policy, provision and research? This project has emerged as a partial answer to that question in relation to the adult numeracy field. It is also contributing to an international project on adult numeracy whose overall purpose is to provide a snapshot of international adult numeracy policy, pedagogy and provision over the last 20 years with case studies of interesting and significant initiatives from a number of countries. While the Australian case study is now complete the remaining research is on-going. [p.1]